Electronegative electroretinogram in the modern multimodal imaging era - Sakti, Dhimas H.; Ali, Haipha; Korsakova, Maria; Saakova, Nonna; Mustafic, Nina; Fraser, Clare L.; Jamieson, Robyn V.; Cornish, Elisa E.; Grigg, John R. (Wiley-Blackwell, 2022)
Background: The electronegative electroretinogram (ERG) reflecting inner retinal dysfunction can assist as a diagnostic tool to determine the anatomical location in eye disease. The aim of this study is to determine the frequency and aetiology of electronegative ERG in a tertiary ophthalmology centre and to develop a clinical algorithm to assist patient management. Methods: Retrospective review of ERGs performed at the Save Sight Institute from January 2011 to December 2020. ERGs were performed according to ISCEV standard. The b:a ratio was analysed in dark adapted (DA) 3.0 or 12.0 recordings. Patients with ratio of ≤1.0 were included. Results: A total of 4421 patients had ERGs performed during study period, of which 139 patients (3.1%) had electronegative ERG. The electronegative ERG patients' median age at referral time was 37 (0.7–90.6) years. The causative aetiologies were photoreceptor dystrophy (48, 34.5%), Congenital Stationary Night Blindness (CSNB) (33, 23.7%), retinal ischemia (18, 12.9%), retinoschisis (15, 10.8%), paraneoplastic autoimmune retinopathy (PAIR) and nonPAIR (14, 10.1%), batten disease (4, 2.9%), and inflammatory retinopathy (4, 2.9%). There were three patients with an unclassified diagnosis. Thirty-two patients (23%) had good vision and a normal fundus appearance. Eleven patients (7.9%) had good vision and normal results in all multimodal imaging. Conclusions: The frequency of electronegative ERG in our referral centre was 3.1% with photoreceptor dystrophy as the main aetiology. A significant number of the cases had good vision with normal fundus or normal multimodal imaging. This further highlights the value of an ERG in this modern multimodal imaging era.